EQUIVALENCE STUDY OF IMMEDIATE RELEASE TABLETS OF BETA BLOCKER DRUG - GABER, DALIA; ABDOUN, SIHAM; MASWADEH, HAMZAH; ALNASSR, EBTIHAL; AL-SALAMAH, MARAM (International Journal of Applied Pharmaceutics, 2020)
Objective: The therapeutic equivalence of generic brands is a great challenge for manufacturers. This study aimed to evaluate the bioequivalence of four different generic brands of atenolol tablets under biowaiver conditions. Methods: Physiochemical properties of the tablet products namely uniformity of weight, hardness, disintegration, and drug content were assessed. The dissolution profiles of atenolol tablets were conducted in pH 1.2, 4.5, 6.8 and 7.6 buffers using USP dissolution apparatus II. Similarity and difference factors were calculated. Finally, four kinetic models have been offered to describe the release characteristics of atenolol under experiment conditions. Results: All tablets showed accepted physiochemical characters. Dissolution profiles revealed that G2 showed the highest similarity to innovator (f2 91.86) in pH 7.6. Dissolution kinetics of G2 at the same pH could be best described as Higuchi model of release. Conclusion: The study showed that excipients and manufacturing practices play an important role in marketing biowaiver generic products meet the international regulatory bodies criteria.